2016
DOI: 10.4062/biomolther.2016.063
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents Identified from Fruit Body of Cordyceps bassiana and Their Anti-Inflammatory Activity

Abstract: Cordyceps bassiana is one of Cordyceps species with anti-oxidative, anti-cancer, anti-inflammatory, anti-diabetic, anti-obesity, anti-angiogenic, and anti-nociceptive activities. This mushroom has recently demonstrated to have an ability to reduce 2,4-dinitrofluorobenzene-induced atopic dermatitis symptoms in NC/Nga mice. In this study, we further examined phytochemical properties of this mushroom by column chromatography and HPLC analysis. By chromatographic separation and spectroscopic analysis, 8 compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The fungal species produces a plethora of secondary metabolites such as bassiacridin, beauvericin, bassianolide and bassianolone (Singh et al 2015). Additionally, C. bassiana , the teleomorph of B. bassiana , produces nucleosides, such as 1,9-dimethylauanine, adenosine, uridine, 3-methyluracil and 1,7-dimethylxanthine (Park et al 2013; Suh et al 2017). In this study, we found that B. bassiana also produce HEA.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal species produces a plethora of secondary metabolites such as bassiacridin, beauvericin, bassianolide and bassianolone (Singh et al 2015). Additionally, C. bassiana , the teleomorph of B. bassiana , produces nucleosides, such as 1,9-dimethylauanine, adenosine, uridine, 3-methyluracil and 1,7-dimethylxanthine (Park et al 2013; Suh et al 2017). In this study, we found that B. bassiana also produce HEA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that the de novo purine nucleotide pathway in C. militaris can produce several nucleosides, such as guanosine, inosine, adenosine, and cordycepin [23]. Another study reported that 1,9-dimethylguanine, adenosine, uridine, nicotinamide, 3-methyluracil, 1,7-dimethylxanthine, nudifloric acid, and mannitol were isolated from CME [24]. To confirm these findings, we conducted a high-performance liquid chromatography (HPLC) assay to verify the presence of nucleosides in CME.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh fruiting bodies for mycelia of C. militaris were extracted with 95% ethanol at room temperature (RT) for 3 days. The extracts were filtered, concentrated, sterilized, and dried as previously described [24]. CME was dissolved in nuclease-free dH 2 O to make a stock solution at 8 mg/mL and stored at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) analysis was used to confirm the phytochemical characteristics of Pc-ME with standard compounds including, quercetin, luteolin, and kaempferol [12], as previously reported [13, 14].…”
Section: Methodsmentioning
confidence: 99%